Analisi Pengaruh Struktur Modal Terhadap Pendapatan Perusahaan Pada PT Bank BNI Syari’ah, Tbk - Iriani I; Puji Muniarty (Ecoplan, 2020)
Abstract - Export is an important component in the economy of the country. The higher the country's export performance, the greater positive effect in increasing of economic growth. From 2012 to 2016, Indonesia's exports continued to decline. Considering these conditions, Indonesia needs to make a strategic effort to increase its export performance, of course. One of the efforts which can be done is conducting export development. As an agricultural country, one of potential commodities used to increase exports is cinnamon. This research will analyze the cinnamon export markets which are potentially to be developed. Moreover, this research will find out the factors that influence the export of these commodities. The methods used are RCA, EPD, X-Model, and Gravity. The result of analysis shows that cinnamon has optimistic markets to be developed in Malaysia, Canada, Netherlands, Brazil, the United States of America, and The Republic of Dominican. Meanwhile, the potential markets to be developed are the United Arab Emirates, Germany and Algeria. The factors affecting exports are gross national product per capita, population, export prices and economic distance. Keywords: EPD, Cinnamon, Gravity Model, Export Development, RCA Abstrak – Bank merupakan suatu lembaga keuangan, untuk melakukan operasinya bank perlu menyediakan modal yang banyak agar tidak berada pada kesulitan keuangan. Maka penulis melihat tidak konstanya struktur modal perbankan dalam menghadapi kerugian. Resiko perbankan dapat terlihat dari tidak optimalnya dalam pengelolaan struktur modal dan pendapatannya. Adapun tujuan penelitian untuk menganalsis pengaruh struktur modal terhadap pendapatan PT Bank BNI Syari’ah, Tbk. Populasi penelitian yaitu 2009-2018 dengan jumlah sampel 7 tahun periode tahun 2012-2018. Jenis penelitian termasuk asosiatif dengan analisa regresi, koefisien korelasi dengan metode kuadrat terkecil. Kesimpulan Penelitian struktur modal tidak berpengaruh dan tidak signifikan terhadap pendapatan pada PT. Bank BNI Syari’ah, Tbk. Kata Kunci : Struktur Modal, Pendapatan, Bank Syariah